PENGARUH KOMPETENSI, INDEPENDENSI, DAN SKEPTISME PROFESIONAL TERHADAP KEMAMPUAN AUDITOR MENDETEKSI KECURANGAN - Affandi, Abigail Marcia Junandi (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2024)
This research aims to see the effect of competence, independence, and professional skepticism on the auditor's ability to detect fraud. This research was conducted using a literature study method obtained from theoretical studies and relevant previous research. The results of this literature study research indicate that competence has a positive effect on the auditor's ability to detect fraud, independence has a positive effect on detecting fraud in auditors, and professional skepticism also has a positive effect on the auditor's ability to detect fraud.